Dry hopping potential of Eureka!, a new hop variety - Schmidt, Christina; Biendl, Martin; Hanke, Stefan; Reglitz, Klaas; Steinhaus, Martin (BrewingScience, 2019)
To monitor the dry hopping potential of the new hop variety Eureka!, brewing trials were performed and observed in detail. Static dry hopping was done for 1, 2, 4, and 8 days. Beers were analyzed using published methods to have an insight into the transfer of 4-MMP (GC×GC-TOFMS, published by Reglitz et al. in BrewingScience 71, 2018), selected hop aroma compounds (EBC 9.49) and hop derived bitter substances (EBC 9.47). Major transfer of 4-MMP and the aroma compounds myrcene, linalool, geraniol, and 2-methylbutyl isobutanoate happened during the first two days of dry hopping with only slight further increase between days 2 and 8. The same behavior could be found for the bitter components alpha-acids and humulinones, whereas xanthohumol increased until day 4. All results of dry-hopped beers allowed a comparison with a lab scale cold-water extraction which was tested as a possible prediction tool for dry hopping of a selected hop variety. In addition to analytics, sensory evaluations were carried out for the beers with help of descriptive analysis. With focus on fruity, especially black currant-like, aroma in beer, the received findings suggest a hop contact time of 2 days of dry hopping with the hop variety Eureka!.